Optimization of Skipjack Tuna (Katsuwonus Pelamis) Quality Factors in Chilled Box Storage Using Taguchi Method - Nika Awalistyaningrum; Jumeri Jumeri; Wahyu Supartono (Agroindustrial Journal, 2023)
Skipjack tuna (Katsuwonus pelamis) is one of tuna fish species in Indonesia,which is perishable and must be kept its freshness by chilling. Aim of this research were to optimize influenced quality factors and to find the best method for reduce deterioration process. The research was conducted by using Taguchi Method, which was used quality robustness concept and multi-performance characteristics to achieve optimal combination of factors. Controlled factors during chilled storage were; weight ratio of ice and fish (A), box size (B), time replacing ice (C), ice form (D), concentration of added salt (E), fish form (F) and number of fishes per kg (G). Quality responses for assessing the freshness were; peroxide value (POV), water content (WC), pH value, texture and Total Plate Count (TPC). The result showed, increase of peroxide value was affected by A of 26.52% and C of 26.52%. Increase of water content was influenced by F of 37.25%. Fluctuation of pH was affected by G of 59.58%. Decrease of texture was influenced by A of 40.47%. Increase of TPC was influenced by A of 31.20%. Priority Scale of factors during storage were A, E, D, G, F, B, and C. Result of analysis muli-performance characteristics gave a conclusion that factors A1, B1, C1, D2, E2, F2 and G2 are the best chilling storage methods.